Atherosclerosis and vasomotor dysfunction in arteries of animals after exposure to combustion-derived particulate matter or nanomaterials. (27th May 2016) - Møller, Peter; Christophersen, Daniel Vest; Jacobsen, Nicklas Raun; Skovmand, Astrid; Gouveia, Ana Cecília Damião; Andersen, Maria Helena Guerra; Kermanizadeh, Ali; Jensen, Ditte Marie; Danielsen, Pernille Høgh; Roursgaard, Martin; Jantzen, Kim; Loft, Steffen
Abstract: Exposure to particulate matter (PM) from traffic vehicles is hazardous to the vascular system, leading to clinical manifestations and mortality due to ischemic heart disease. By analogy, nanomaterials may also be associated with the same outcomes. Here, the effects of exposure to PM from ambient air, diesel exhaust and certain nanomaterials on atherosclerosis and vasomotor function in animals have been assessed. The majority of studies have used pulmonary exposure by inhalation or instillation, although there are some studies on non-pulmonary routes such as the gastrointestinal tract. Airway exposure to air pollution particles and nanomaterials is associated with similar effects on atherosclerosis progression, augmented vasoconstriction and blunted vasorelaxation responses in arteries, whereas exposure to diesel exhaust is associated with lower responses. At present, there is no convincing evidence of dose-dependent effects across studies. Oxidative stress and inflammation have been observed in the arterial wall of PM-exposed animals with vasomotor dysfunction or plaque progression. From the data, it is evident that pulmonary and systemic inflammation does not seem to be necessary for these vascular effects to occur. Furthermore, there is inconsistent evidence with regard to altered plasma lipid profile and systemic inflammation as a key step in vasomotor dysfunction and progression of atherosclerosis in PM-exposed animals. In summary, the results show that certain nanomaterials, including TiO2, carbon black and carbon nanotubes, have similar hazards to the vascular system as combustion-derived PM.